Detection of Semantically Equivalent Fragments for Business Process Model Change Management - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 7th International Conference on Services Computing (SCC'10))

Enriching RUP with key success factors for large-scale custom software development projects - Heinemann, Marianne; Duwe, Bettina; Engels, Gregor (Software & Systems Engineering Essentials (SEE) 2010)

Auswahl projektspezifischer Vorgehensstrategien - Heinemann, Marianne; Engels, Gregor (Integration von Vorgehensmodellen und Projektmanagement)

Computergestützte traumatherapeutische Behandlungsmöglichkeiten bei Verkehrsunfallopfern von Kinder und Jugendlichen - Huck, Wilfried; Alakbarov, Alexej; Domik, Gitta; Radkowski, Rafael; Tölke, Roswitha; Mikus, Ann-Cathrin; Geisen, Silke (12. Jahrestagung der Deutschsprachigen Gesellschaft für Psychotraumatologie (DeGPT))

Dynamic Computation of Change Operations in Version Management of Business Process Models - Küster, Jochen; Gerth, Christian; Engels, Gregor (Proceedings of the 6th European Conference on Modelling Foundations and Applications (ECMFA'10))
Version management of business process models requires that changes can be resolved by applying change operations. In order to give a user maximal freedom concerning the application order of change operations, position parameters of change operations must be computed dynamically during change resolution. In such an approach, change operations with computed position parameters must be applicable on the model and dependencies and conflicts of change operations must be taken into account because otherwise invalid models can be constructed. In this paper, we study the concept of partially specified change operations where parameters are computed dynamically. We provide a formalization for partially specified change operations using graph transformation and provide a concept for their applicability. Based on this, we study potential dependencies and conflicts of change operations and show how these can be taken into account within change resolution. Using our approach, a user can resolve changes of business process models without being unnecessarily restricted to a certain order.

A Meta-Method for Defining Software Engineering Methods - Engels, Gregor; Sauer, Stefan (Graph Transformations and Model-Driven Engineering)

Erweiterung des TPI-Modells zur Reifegradbewertung unter Berücksichtigung von projekteigenen Anforderungen - Sancar, Yavuz; Schumacher, Claudia (Proceedings of the Conference on Software & Systems Engineering Essentials 2010 (SEE 2010), Köln (Germany))

Assessments in Global Software Development: A Tailorable Framework for Industrial Projects - Salger, Frank; Engels, Gregor; Hofmann, Alexander (Proceedings ACM/IEEE 32nd International Conference on Software Engineering, Software Engineering in Practice Track, Cape Town, South Africa (ICSE'10))

SheetDiff: A Tool for Identifying Changes in Spreadsheets - Chambers, Chris; Erwig, Martin; Luckey, Markus (Proceedings of the 26th IEEE Symposium on Visual Languages and Human-Centric Computing 2010 (VL/HCC 2010))

Model-driven Development of Advanced User Interfaces - Van den Bergh, Jan; Meixner, Gerrit; Breiner, Kai; Pleuß, Andreas; Sauer, Stefan; Hussmann, Heinrich (Proc. 28th International Conference on Human Factors in Computing Systems (CHI 2010))